Burn and mechanical residue removal methods on production‐life of Kentucky bluegrass. Issue 3 (25th June 2022) - Holman, Johnathon D.; Robertson, Jack D.; Johnson‐Maynard, Jodi; Painter, Kathleen; Assefa, Yared
Abstract: Given the importance of Kentucky bluegrass ( Poa pratensis L.) seed production in the inland Pacific Northwest, USA, and the difficulty to predict and maintain seed yields as production fields age, greater knowledge of the impact of reduced or nonthermal practices on seed yield and stand longevity is necessary. Longer‐term studies (>3 yr) are needed to maintain high bluegrass seed yields, reduce soil erosion, and amortize the expense of stand establishment. The purpose of this study was to measure the impact of residue management practice on seed production throughout the expected 7‐yr life of a bluegrass field. Four residue management treatments—full load burn (FLB), bale then burn (BB), bale then mow then harrow (MEC), and rotation system (SYS) (MEC in Year 1, BB in Year 2, and FLB in Year 3)—were evaluated from 2002–2007. Average seed yields over the entire study period were 774 kg ha –1 in FLB, 742 kg ha –1 in BB, 525 kg ha –1 in MEC, and 600 kg ha –1 in SYS. Nonstanding residue removal was difficult to accomplish using MEC compared with FLB. Reduced‐burn methods (BB and SYS), however, were able to keep this residue level lower than MEC, and therefore yielded more than MEC. Across‐treatment regression suggest that seed yield was negatively influenced by the amount of nonstanding residue in the previous fall ( r 2  = .64), yet positively influenced by the nitrogen content of standing biomass in the previous fall ( r 2  = .78). Profitability was highest in BB and FLB. Overall, understanding the factors that relate to stand decline may help growers prolong stand life and increase profitability, while mitigating air quality issues. Core Ideas: Seed yields were the greatest in full load burn, followed by bale then burn treatments. Seed yield was negatively influenced by nonstanding residue and positively by N content of fall standing biomass. Like seed yield, profitability was also greatest in bale then burn and full load burn treatments, Profitability of mechanical management practices is dependent on highly variable forage and feed prices.